2005
DOI: 10.1007/s00595-005-3009-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Intraoperative Heart Failure Caused by Ampulla Cardiomyopathy by Intra-aortic Balloon Pumping and Percutaneous Cardiopulmonary Support: Report of a Case

Abstract: An 82-year-old woman underwent total gastrectomy for advanced gastric cancer with invasion to the lower esophagus. Her blood pressure dropped alarmingly during the operation, which was performed via the transabdominal and left-side transthoracic approach. Using echocardiography, we diagnosed intraoperative-onset reversible heart failure caused by ampulla cardiomyopathy. Because the infusion of catecholamines is associated with secondary heart failure, we gave her calcium antagonists and nicorandil, then starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Yabuuchi et al [4] reported a patient with takotsubo cardiomyopathy who developed cardiogenic shock resistant to an intravenous administration of catecholamine and who needed a mechanical support with intra-aortic balloon pumping. In this patient, the administration of catecholamine may have enhanced the dynamic mid-ventricular obstruction, leading to prolonged cardiogenic shock, although the IVPG was not described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Yabuuchi et al [4] reported a patient with takotsubo cardiomyopathy who developed cardiogenic shock resistant to an intravenous administration of catecholamine and who needed a mechanical support with intra-aortic balloon pumping. In this patient, the administration of catecholamine may have enhanced the dynamic mid-ventricular obstruction, leading to prolonged cardiogenic shock, although the IVPG was not described in this paper.…”
Section: Discussionmentioning
confidence: 99%